SYMBOLS IN THE STRUCTURE OF MELAY POETRY : THE STUDY OF TREATMENT CHARMS - Kurmalasari, Tety; Muhammad Candra (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2022)
The purpose of this study is to examine or reveal about the symbols and meanings of the symbols contained in the healing spell. The theory used in this research is the semiotic theory of the signifier and the signified and the symbol theory which analyzes the object representing a symbol. The method used is descriptive qualitative method, namely interviews with five informants as resource persons for spells which are solely to describe empirical facts or language phenomena that exist in life. The results of this study indicate that the symbols contained in the healing mantra are Tuan Putri seven, one hundred and ninety, kantan and reed, twigs, bidara leaves, iron chests, light of Allah, light of Muhammad, Hati tik Hati, points of heavy rain falling, rising and falling. laughter, betel nut, I'm elephant Ali's eyes stretched a few bones. etc.